2010
DOI: 10.3168/jds.2009-2967
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bile salts stress on protein synthesis of Lactobacillus casei Zhang revealed by 2-dimensional gel electrophoresis

Abstract: Lactobacillus casei Zhang, isolated from koumiss in Inner Mongolia of China, is known from previous findings to be tolerant to bile salts. Bile salts secreted by mammals act as a natural antibacterial barrier and may serve as a component of innate immunity, as they have limited antagonistic effect against resident microflora. In this work, we compared the growth and protein expression patterns of L. casei Zhang with and without bile salts. Twenty-six proteins were found to be differentially expressed using 2-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 42 publications
(49 reference statements)
1
45
1
Order By: Relevance
“…However, at the transcriptional level, no significant differences were observed in any of the genes encoding the subunits of the ATPase. Wu et al (2010) did not observe this effect, whereas Hamon et al (2012) observed modest increments in the abundance of subunit d in some L. casei strains. However, it cannot be ascertained whether this is due to different experimental designs or methodologies.…”
Section: Cell Envelope-related Functionsmentioning
confidence: 81%
See 4 more Smart Citations
“…However, at the transcriptional level, no significant differences were observed in any of the genes encoding the subunits of the ATPase. Wu et al (2010) did not observe this effect, whereas Hamon et al (2012) observed modest increments in the abundance of subunit d in some L. casei strains. However, it cannot be ascertained whether this is due to different experimental designs or methodologies.…”
Section: Cell Envelope-related Functionsmentioning
confidence: 81%
“…Activation of stress proteins in response to bile has been observed in L. casei Zhang (Wu et al, 2010) and its close relative L. rhamnosus GG (Koskenniemi et al, 2011). In contrast, a clear activation of stress proteins was not observed by Hamon et al (2012).…”
Section: Stress Responsementioning
confidence: 84%
See 3 more Smart Citations